The Development of an AAV-Based CRISPR SaCas9 Genome Editing System That Can Be Delivered to Neurons in vivo and Regulated via Doxycycline and Cre-Recombinase - Kumar, Namrata; Stanford, William; de Solis, Christopher; Aradhana,; Abraham, Nigel D.; Dao, Trieu-Mi J.; Thaseen, Sadiqa; Sairavi, Anusha; Gonzalez, Cuauhtemoc Ulises; Ploski, Jonathan E. (Frontiers in Molecular Neuroscience, 2018)
The RNA-guided Cas9 nuclease, from the type II prokaryotic Clustered Regularly Interspersed Short Palindromic Repeats (CRISPR) adaptive immune system has been adapted by scientists to enable site specific genome editing of eukaryotic cells both in vitro and in vivo. Previously, we reported the development of an Adeno-Associated Virus (AAV) mediated CRISPR S. pyogenes (Sp) Cas9 system, in which the genome editing function can be regulated by controlling the expression of the guide RNA (sgRNA) in a doxycycline (Dox) dependent manner. Here, we report the development of an AAV vector tool kit utilizing the Cas9 from S. Aureus (SaCas9). We demonstrate in vitro genome editing in human derived 293FT cells and mouse derived Neuro2A (N2A) cells and in vivo in neurons of the mouse brain. We also demonstrate the ability to regulate the induction of genome editing temporally with Dox and spatially with Cre-recombinase. The combination of these systems enables AAV mediated CRISPR/Cas9 genome editing to be regulated both spatially and temporally.